MULTI-CRITERIA DECISION-MAKING FOR ELECTRIC BICYCLE SELECTION - Trinh Van Huy; Nguyen Quang Quyet; Vu Huu Binh; Tran Minh Hoang; Nguyen Thi Thuy Tien; Le Tuan Anh; Dao Thi Nga; Nguyen Quoc Doan; Pham Hoang Tu; Do Duc Trung (Advanced Engineering Letters, 2022)
Electric bicycle is a vehicle which is used widely in all the citys and provinces of Vietnam. However, it’s hard to choose “the most suitable” or “the best” type of electric bicycle because each type has different criteria (parameters). To choose out the best option, we need to consider all the alternatives at once. That is called multi-criteria decision-making. This research used three multi-criteria decision-making methods include SAW method, MARCOS method and PSI method to choose from seven bestselling types of electric bicycle on the market in 2022. All the methods which were used chose out the same best electric bicycle type and the same worst bicycle type. And so, among seven types of electric bicycle which include M133 mini, M133 Sport 2022, Aima 133AM, Nijia – PA4, DK 133M, Yadea iGo and Yadea i3, the best type is Aima 133AM, in contrast, Yadea iGo is considered the worst type. Things that need to be done in the folowing researches were proposed in the last part of this paper.